Efforts to Improve the Development of Naturalistic Intelligence through Outbound Methods at RA Muslimat NU XVII Keser Kec. Tunjungan Kab. Blora - Mufid, Abdul; Fatimah, Siti; Umar, Jamilu Abdullahi; Mawere, Daniel (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
The naturalistic intelligence of early childhood is very important to be stimulated because at an early age child are faster to receive stimuli and apply the knowledge or knowledge they have acquired. One way to stimulate is through the outbound method. The naturalistic intelligence of grade B children at RA Muslimat NU XVII Keser, Tunjungan, and Blora has not yet been achieved and developed. Therefore, this study analyzes efforts to improve children's naturalistic intelligence through the outbound method. The type of method used by the researcher is qualitative, namely using analysis of interview data and in-depth observations in the field. From the data sources that the researchers got from the field, the researchers were able to formulate a problem statement on how to apply increasing naturalistic intelligence through the outbound method at RA Muslimat NU XVII Keser, Kec. Tunjungan, Blora? to increase naturalistic intelligence in children. The results of this study indicate an increase in the naturalistic intelligence of class B children RA Muslimat NU XVII Keser, Tunjungan, and Blora.